High‐fat diet induces cardiac remodelling and dysfunction: assessment of the role played by SIRT3 loss. Issue 8 (17th March 2015) - Zeng, Heng; Vaka, Venkata Ramana; He, Xiaochen; Booz, George W.; Chen, Jian‐Xiong
Abstract Mitochondrial dysfunction plays an important role in obesity‐induced cardiac impairment. SIRT3 is a mitochondrial protein associated with increased human life span and metabolism. This study investigated the functional role of SIRT3 in obesity‐induced cardiac dysfunction. Wild‐type (WT) and SIRT3 knockout (KO) mice were fed a normal diet (ND) or high‐fat diet (HFD) for 16 weeks. Body weight, fasting glucose levels, reactive oxygen species (ROS) levels, myocardial capillary density, cardiac function and expression of hypoxia‐inducible factor (HIF)‐1α/‐2α were assessed. HFD resulted in a significant reduction in SIRT3 expression in the heart. Both HFD and SIRT3 KO mice showed increased ROS formation, impaired HIF signalling and reduced capillary density in the heart. HFD induced cardiac hypertrophy and impaired cardiac function. SIRT3 KO mice fed HFD showed greater ROS production and a further reduction in cardiac function compared to SIRT3 KO mice on ND. Thus, the adverse effects of HFD on cardiac function were not attributable to SIRT3 loss alone. However, HFD did not further reduce capillary density in SIRT3 KO hearts, implicating SIRT3 loss in HFD‐induced capillary rarefaction. Our study demonstrates the importance of SIRT3 in preserving heart function and capillary density in the setting of obesity. Thus, SIRT3 may be a potential therapeutic target for obesity‐induced heart failure.